128 Increased Carotid Plaque Neovascularization, a Marker of Plaque Vulnerability, is Independently Associated with South Asian Ethnicity: A Possible Mechanism Underlying the Greater Burden of Cardiovascular Events in South Asians vs Northern Europeans. (6th June 2015) - Senior, Roxy; Shah, Benoy; Chahal, Navtej; Anantharam, Brijesh; Kooner, Jaspal
Abstract : Background: The mechanisms behind the excess of cardiovascular events (CVE) in South Asians compared with native Europeans are unclear. The burden of sub-clinical carotid atherosclerosis is an established CVE prognosticator, but we recently found no differences between asymptomatic South Asians and Europeans. Thus, we hypothesised that a difference in plaque vulnerability (PV) may explain the increased CVE. Intraplaque neovascularization (IPN) is a pre-cursor of plaque haemorrhage and thus a surrogate marker of PV. Contrast enhanced ultrasound (CEUS) of the carotid arteries allows accurate visualisation of IPN. Methods: Subjects were drawn from the London Life Sciences Population ( LOLIPOP ) study comparing European and South Asian populations. Subjects with plaques on initial scanning were recalled for CEUS imaging, using Sonovue contrast. Presence of IPN was judged visually and logistic regression used to identify independent predictors of IPN. Results: A total of 175 subjects underwent carotid imaging. Mean age was 64.7 ± 8.9 yrs. There were 96 European (55%) and 79 South Asian (45%) subjects, in whom 197 and 170 plaques were noted respectively. On a per-patient basis, IPN was seen in 56/79 (71%) Asian and 55/96 (57%) European subjects. After adjustment for clinical variables, South Asian ethnicity was the only independent predictor of IPN (OR 2.8, 95% C. I. 1.36–5.92, p = 0.006). Conclusions: This is the first study to show that IPN is independently associated with South Asian ethnicity. As a marker of PV, this may account for the higher CVE observed in South Asians vs. Europeans. Larger studies are required to confirm these preliminary data.